PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DENGAN VARIABEL SEMANGAT KERJA SEBAGAI MEDIASI PADA PT. LUTVINDO WIJAYA PERKASA PEKANBARU RIAU - zanra, sri wahyuni (Journal of Management and Business, 2023)
This research aims to determine the influence of the work environment and work morale on the performance of Lutvindo Wijaya Perkasa Pekanbaru Riau employees and to determine the influence of the work environment on employee performance through the work spirit of Lutvindo Wijaya Perkasa Pekanbaru Riau employees. population at PT. Lutvindo Wijaya Perkasa Pekanbaru has 155 employees. Meanwhile, the sampling technique used a formula from Slovin to obtain a sample of 61 respondents. The research results show that the work environment does not have a significant effect on employee performance at Lutvindo Wijaya Perkasa Pekanbaru Riau. However, work enthusiasm has a direct and significant influence on employee performance at Lutvindo Wijaya Perkasa Pekanbaru Riau. And also towards the work spirit of employees at Lutvindo Wijaya Perkasa Pekanbaru Riau. Based on the research results, it was also concluded that work enthusiasm was able to mediate the relationship between the work environment and employee performance at Lutvindo Wijaya Perkasa Pekanbaru Riau..